Fostering Students’ Critical Thinking through Socratic Seminar - Nurul Hasanah; Deddy Suezdi (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
Student of 21st century have a basket of challenge. They must be able to think critically, to communicate effectively, to collaborate respectfully, and to think creatively. Those four Cs are not a school subject that will be teach independently. Yet, all of them are integrated on each subject that the students' learnt. Among those four, critical thinking is an emergency necessity for college students to help them develop their original thesis report. Through a classroom action research, Socratic Seminar will introduce in Exploring Poetry and Prose subject to foster students' critical thinking skills. The aims of this paper is to find out to what extend Socratic Seminar foster students’ critical thinking. Observation, interview, and questionnaire are used to collect the data. To sum up, Socratic Seminar successfully developed students' thinking from equilibrium to disequilibrium to a more sophisticated equilibrium. Keywords: Critical thinking, Socratic seminar